2021
DOI: 10.31389/jltc.85
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Ownership Status of Nursing Homes and Their Outcomes During the COVID-19 Pandemic: A Rapid Literature Review

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has exposed several cracks in our healthcare, social care and long-term care systems. The nursing home sector, in particular, has been disproportionally affected by the COVID-19 virus (Comas-Herrera & Zalakain, 2020). In a study of 22 countries, an alarming 41% of their COVID-19 related deaths occurred in nursing homes, while only, on average, 0.7% of the total population live in nursing homes (Comas-Herrera et al., 2021). Nursing home residents are ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“… Bos et al (2017) argued that work well-being was better in non-profit nursing homes, but their results were limited to the United States and primarily emphasized staffing levels and resident well-being. Similarly, a rapid review found a relationship between for-profit incentives and increased COVID-19 cases and the number of deaths among nursing home residents ( Kruse et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Bos et al (2017) argued that work well-being was better in non-profit nursing homes, but their results were limited to the United States and primarily emphasized staffing levels and resident well-being. Similarly, a rapid review found a relationship between for-profit incentives and increased COVID-19 cases and the number of deaths among nursing home residents ( Kruse et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed by Banerjee et al (2021) , enforcing stricter staffing-level regulations to combat incentives to cut the workforce could be one option. Kruse et al (2021) discussed different approaches: disincentivizing for-profit ownership, favoring non-profit ownership, and demanding higher minimum staffing standards. Another suggestion has been to demand transparency through reporting on financial and quality outcomes and on how resources are utilized, with the possible addition of regulated cost controls ( Harrington et al, 2017 ; Ronald et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We focused on mapping which types of interventions were studied during the pandemic but did not attempt to systematically synthesise findings on the effectiveness of these. Other reviews have systematically synthesised available evidence on the effects of specific interventions or other factors that could explain variations in outcomes (Kruse et al, 2021;National Collaborating Centre for Methods and Tools, 2021).…”
Section: Limitationsmentioning
confidence: 99%
“…NHs affiliated with a multi-facility chain may have different organizational structures and pandemic responses to PPE shortages than non-chain facilities. 18,19 One study found that chain affiliation was associated with a higher probability of PPE shortages in June-July of 2020. 8 This disadvantage may make financial resources more important to chain-affiliated NHs, suggesting that chain affiliation can potentially moderate the association of financial performance with PPE shortages.…”
Section: Introductionmentioning
confidence: 99%